2022
DOI: 10.1111/mpp.13225
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of cell wall integrity pathway phosphorylation is required for the growth and pathogenicity of Magnaporthe oryzae

Abstract: In M. oryzae, the cell wall integrity (CWI) pathway consists of the MAP kinase kinase kinase (MoMck1), the MAP kinase kinase (MoMkk1), and the MAP kinase (MoMps1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…However, constitutively activated CWI signaling disrupts the balance between growth and stress response. Previous studies also showed that phosphatases MoPtc1 and MoPtc2 dephosphorylate MoMkk1 to switch off CWI signaling ( 13 ). Moreover, studies indicated that the MAPK cascade plays a role in CWI signaling and autophagy, which is regulated by MAPK pathways in response to external stimuli or environmental conditions ( 14 ).…”
Section: Introductionmentioning
confidence: 89%
“…However, constitutively activated CWI signaling disrupts the balance between growth and stress response. Previous studies also showed that phosphatases MoPtc1 and MoPtc2 dephosphorylate MoMkk1 to switch off CWI signaling ( 13 ). Moreover, studies indicated that the MAPK cascade plays a role in CWI signaling and autophagy, which is regulated by MAPK pathways in response to external stimuli or environmental conditions ( 14 ).…”
Section: Introductionmentioning
confidence: 89%
“…The plant cell wall, a complex network of polysaccharides, including cellulose, hemicellulose, and pectin ( 3 5 ), is the initial physical and defensive barrier against a variety of biological stresses and is thus an important site of host-pathogen interaction ( 5 , 6 ). Plant cell walls usually participate in the immune response via dynamic remodeling to prevent pathogen infection ( 7 ); the plant cell wall also senses external stressors and transmits signals to stimulate defensive responses in the host ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%